Keys to sustainable da‘wah leadership - Bensaid, Benaouda (2010)

(untitled)
More than any other time, contemporary da‘wah management models are in dire need for a better sustainable leadership. Such a need is justified by the global shift to sustainable quality, da‘wah loss or retreat endured in the absence of strategic thinking and positive leadership, not to forget about the impact of modernity on the da‘wah methodology and strategy. Developing sustainable da‘wah leadership, not only provides us with the potential required to excel in da‘wah planning, organization and execution, or strengthen the sense of brotherhood and unity, but equally promotes a universal approach leading to collective and powerful societal changes. This development however, should be understood in terms of a new relevant da‘wah framework in which related concepts, guidelines, ethics and principles are well defined and positioned in the broader and strategic scale of sustainable leadership. The current paper seeks to explore the theoretical framework needed for developing a sustainable da‘wah leadership in contemporary societies. It sheds light on some basic issues of da‘wah including the development of da‘wah human capacity (DHC), da‘wah outcome driven action (DODA), da‘wah strategic alliances (DNSA) and standardized da‘wah managements (SDM).